Elzalia heterospiculata sp. nov. (Nematoda: Monhysterida: Xyalidae) from the South China Sea - Jia, Susu; Huang, Yong (Zootaxa, 2019)
A new free-living marine nematode species of the genus Elzalia belonging to the family Xyalidae is described from the seabed sediment of the northeast region of the South China Sea. Elzalia heterospiculata sp. nov. is characterized by elongated spicules unequal in length, left spicule prominently longer than right spicule, ratio of body length to spicule length is 4.7–6.2; complex gubernaculum consisting of four sections, apophyses clavate, 12–14 µm long; and amphideal fovea positioned near the top of the head. It is similar to E. federici Castillo-Fernandez and Lambshead, 1990 and E. floresi Gerlach, 1957. However, the new species differs from the similar two species in having markedly unequal spicules, complex gubernaculum consisting of four sections, amphideal fovea close to the top of the head. Updated key to all species of Elzalia is provided.